Arquitetura pedagógica para groupwares baseada no pensamento freinetiano com suporte avaliativo em representações sociais de abordagem estrutural - Ferrari, Hélio Oliveira (2017)
One of the factors that hinders the issue of innovation in Brazil is the fact of training for the world of work in a society immersed in a Digital Culture. . Thus, mitigating this difficulty involves education. It is understood here that project methodology is a point of intersection between formal education and the world of work. In this way, it was tried to elaborate a Pedagogical Architecture oriented to the management of projects containing the possibility of diagnostic evaluations through the Theory of Social Representations. The Pedagogical Architecture is understood as a set of strategies, software and tools of support to the cooperation that can favor the learning. It was established that the technological aspect of the Architecture would be filled by the elaboration of an unprecedented application for the project management. This application was modeled by a reference architecture within an MVC pattern project. The methodological aspect of the Pedagogical Architecture is given by work plans, a technique of Freinet Pedagogy. And the Freinet Pedagogy, for its aspects of a cooperative education, focused on the education of work, focused on the interests of the student and that through the experimental groping has its proposal of learning occupies the organizational aspect of Architecture. The architecture was constructed demonstrating the actuality of the Freinet pedagogy within the digital culture, being based the social representations as an evaluation proposal for collective environments and prototyping the application for project management.